Understanding and targeting alkylator resistance in glioblastoma - Wick, Wolfgang; Platten, Michael (Cancer discovery, 2014)
Summary: Alkylating chemotherapy is the mainstay in the treatment of pediatric and adult glioblastoma despite primary and acquired resistance and scientific efforts to precisely define therapies for individual patients. A focus on non-MGMT-mediated temozolomide resistance for pediatric glioblastoma suggests options for new drug combinations. Cancer Discov; 4(10); 1120-2. ©2014 AACR. - See related article by Agnihotri et al., p. 1198